A reforma trabalhista e a concessão do benefício da justiça gratuita como garantia de acesso à justiça - Patricio, Yônária Alves (Universidade Federal do Tocantins, 2021)
The following article refer to labour law reformulation and the concession of the free justice benefit, also the rights warranty of justice access. This article aimed to study and answering the changes occurred in the granting of free justice benefit as a result of the labor law reformulation, and if whether these changes has restricted or expanded of the worker's access to the justice system aiming analyze if these changes has preserved the constitutional right of justice access. This article has been done based on a theoretical research using the descriptive method with a qualitative approach, with bibliographic research on labor law doctrines and labor process, on official sites, such as “Portal do Tribunal Superior do Trabalho” (The Superior Labor Court web site), on the Federal Constitution, and also on the CLT - Consolidação das Leis do Trabalho (Labor Laws Consolidation) and the changes coming from Law 13.467/2017. This is a very significant and relevance study, that aims to disseminate knowledge about these subject, bringing information of changes in the rules concession of free justice benefit and the consequences that has caused by the Labor Law Reformulation on this benefit. It can be noted that, as a result of this changes has brought trouble hindered workers from seek Labor Justice, even though they are beneficiaries of free justice, they may bear the economic burden. Thus, the unconstitutionality of the provisions is defended, because by analyzing the restrictions imposed on the gratuity of justice, it can be affirmed that the Reform radically hurts the Federal Constitution in several aspects, and ends up being a step backwards in labor justice bringing the workers a very vulnerable situation.